Beyond the blogosphere information and its children - Barlow, Aaron, 1951- (Praeger, 2012)
"This book looks at questions and answers pertaining to the organization, usage, and ownership of information in the Internet age--and the impact of shifting attitudes towards information ownership on creative endeavors"--